The Oxford history of the laws of England. Volume II, 817-1216 - Hudson, John, 1962- (Oxford : Oxford University Press, 2012)
By 1216 the foundations of the English common law had been laid. This book assesses the development of law and society during the preceding three centuries, analysing the great legacy of the Anglo-Saxon realm, the impact of Norman custom and the energetic contribution of the 12th cenury Kings.
Description based on online resource; title from home page (viewed on July 12, 2012).
Includes bibliographical references and index.
Keywords: Law, Medieval; Law -- England -- History -- To 1500.